2019
DOI: 10.1080/00949655.2019.1607345
|View full text |Cite
|
Sign up to set email alerts
|

Model selection in high-dimensional noisy data: a simulation study

Abstract: In many practical applications, high-dimensional regression analyses have to take into account measurement error in the covariates. It is thus necessary to extend regularization methods, that can handle the situation where the number of covariates p largely exceed the sample size n, to the case in which covariates are also mismeasured. A variety of methods are available in this context, but many of them rely on knowledge about the measurement error and the structure of its covariance matrix. In this paper we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We followed the procedures described in Sørensen et al (2015), Nghiem and Potgieter (2019) and Romeo and Thoresen (2019) to process the raw data using the BGX package of Hein et al (2005), and assumed the measurement error on each gene was mutually independent from that on the other. As a result, the measurement error covariance matrix Σ u was set to be diagonal.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed the procedures described in Sørensen et al (2015), Nghiem and Potgieter (2019) and Romeo and Thoresen (2019) to process the raw data using the BGX package of Hein et al (2005), and assumed the measurement error on each gene was mutually independent from that on the other. As a result, the measurement error covariance matrix Σ u was set to be diagonal.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Another approach for handling measurement error is to modify the loss function or the conditional score functions commonly seen in the error-free penalized regressions; examples include the corrected lasso method of Loh and Wainwright (2012) and Sørensen et al (2015), and the convex conditioned lasso of Datta et al (2017). More recently, Romeo and Thoresen (2019) presented a simulation study to compare the performance of the MU, corrected lasso, and convex conditioned lasso against the naive estimator in both estimation and variable selection; they concluded that the relative performance of those estimators depend on the structure of Σ u . Brown et al (2019) introduced a boosting algorithm based on the estimating equation of the corrected lasso, but the theoretical properties of the final estimates were not examined.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a distinctive feature of the Affymetrix microarray data set is that multiple probes are used to measure each gene expression; hence, these replicated measurements can be used to estimate the covariance matrix of measurement errors 𝚺 𝑢 . We followed the procedures described in Sørensen et al (2015), Nghiem and Potgieter (2019), and Romeo and Thoresen (2019) to process the raw data using the BGX package of Hein et al (2005), and assumed the measurement error on each gene was mutually independent from that on the other. As a result, the measurement error covariance matrix 𝚺 𝑢 was set to be diagonal.…”
Section: Analysis Of Microarray Datamentioning
confidence: 99%
“…We followed the procedures described in Sørensen et al. (2015), Nghiem and Potgieter (2019), and Romeo and Thoresen (2019) to process the raw data using the BGX package of Hein et al. (2005), and assumed the measurement error on each gene was mutually independent from that on the other.…”
Section: Analysis Of Microarray Datamentioning
confidence: 99%
See 1 more Smart Citation